Five comparing transitions to fatherhood across contexts - Plantin, L.; Guerreiro, M. D.; Bäck-Wiklund, M.; Kovacheva, S. (Transitions to parenthood in Europe: A comparative life course perspective, 2012)
The chapter partly mirrors the previous chapter on transitions to motherhood but also emphasises the importance of gendered institutional frameworks that affect mothers and fathers differently. Cases from Bulgaria, Sweden and Portugal are compared. Special attention is paid to the transition to fatherhood in relation to other life course transitions such as school leaving, gainful employment, moving out of parental household. Life lines are analysed and set in context of national age based transition patterns and other structural characteristics. Interpretations and reflections provided by the interviewees about the course of their lives are analysed and compared. Gender shapes parenthood. Fathers are in many instances still expected to be the main economic providers and are thus expected to give the career and work life high priority. In addition to variation across national contexts, social class also impact on experiences of the transition to fatherhood.